2012
DOI: 10.14331/ijfps.2012.330034
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Activity Concentration of Natural Radionuclide of Building Materials in Kochi

Abstract: The study of natural radiation exposure is of importance because it accounts for the largest contribution to the collective dose for the world population from all sources. Extent of exposure to natural radiation depends on the occupation, type of dwelling, location of habitation, and lifestyle of the population. All building materials contain various amounts of natural radionuclides as they are derived from the rocks and soils, which always contain natural radionuclides of Uranium ( 238 ), and Thorium ( ℎ) 232

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Most building materials derived from rocks and soils, which always contain natural radionuclides of Uranium ( 238 ), and Thorium ( 232 ℎ) series. The radioactive isotope of Potassium ( 40 ), which give both external and internal radiation exposure to the inhabitants of dwellings built with such materials(Dhanya Balakrishnan, Abraham, Rajagopalan, & Jojo, 2012) in which the gamma radiation arising from the walls, floors and ceilings, and Radon and Thoron and their progeny are the major sources of radiation exposures. Previous studies around the world have indicated the presence of natural radionucliudes in different types of building materials: Marbles in Pakistani (Aslam, Orfi, Khan, & Jabbar, 2002), concrete blocks from Nigeria in Ibadan (Ademola & Oguneletu, 2005), Portland cement used in Nigeria (Ademola, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most building materials derived from rocks and soils, which always contain natural radionuclides of Uranium ( 238 ), and Thorium ( 232 ℎ) series. The radioactive isotope of Potassium ( 40 ), which give both external and internal radiation exposure to the inhabitants of dwellings built with such materials(Dhanya Balakrishnan, Abraham, Rajagopalan, & Jojo, 2012) in which the gamma radiation arising from the walls, floors and ceilings, and Radon and Thoron and their progeny are the major sources of radiation exposures. Previous studies around the world have indicated the presence of natural radionucliudes in different types of building materials: Marbles in Pakistani (Aslam, Orfi, Khan, & Jabbar, 2002), concrete blocks from Nigeria in Ibadan (Ademola & Oguneletu, 2005), Portland cement used in Nigeria (Ademola, 2008).…”
Section: Introductionmentioning
confidence: 99%